Green synthesis and characterization of silver nanoparticles using leaf extract of aloe vera - Ojonukpe, Omotoyosi; Ibrahim Olakunle shoetan (IJRDO-Journal of Applied Science, 2020)
For this research, a novel approach has been carried out for the green synthesis of silver Nano particle using leaf extract of Aloe Vera and silver nitrate solution. Stable silver nanoparticles were formed by treating aqueous solution of AgNO 3 with the plant leaf extracts as reducing agent of Ag + to Ag 0 . UV-visible spectroscopy was used to monitor the quantitative formation of silver nanoparticles and this show a peak at 410 nm. The synthesized silver nanoparticles were characterized using scanning electron microscopy (SEM) and Fourier Transform Infra-red Spectroscopy (FTIR). The average particle size ranged from 300 to 410 nm. The particle size could be controlled by changing the reaction temperature, leaf broth concentration and AgNO 3 concentration. This eco-friendly method of synthesizing silver nanoparticles production provides rates of synthesis which is more efficient when compared to those of chemical methods and can applied in various human endeavours such as cosmetics, foods and medical applications.